1973
DOI: 10.1159/000152553
|View full text |Cite
|
Sign up to set email alerts
|

Dermatoglyphs of the South African Negro

Abstract: Data from 200 male and 200 female South African Negroes’ finger and palm prints are presented. The subjects were apparently normal volunteers who belonged to the Zulu ethnic group. The frequency distributions of finger print pattern types, digital and total ridge counts, a–b scores and atd angles are given. The Zulus have a lower mean total ridge count than the other races of the Durban area; in males it is 129.87 and in females, 119.62.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
1

Year Published

1975
1975
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
2
3
1
Order By: Relevance
“…Another study on sub-Saharan Africans has also shown that the values of TFRC found among the Zimbabweans were higher in men than in women (Igbigbi and Msamati, 2002). These results were also comparable to those obtained in the Zulus of South Africa (Grace and Ally, 1973). The Southern Nigerians have a significantly higher TFRC than those previously reported for the Zulu.…”
Section: Discussionsupporting
confidence: 90%
“…Another study on sub-Saharan Africans has also shown that the values of TFRC found among the Zimbabweans were higher in men than in women (Igbigbi and Msamati, 2002). These results were also comparable to those obtained in the Zulus of South Africa (Grace and Ally, 1973). The Southern Nigerians have a significantly higher TFRC than those previously reported for the Zulu.…”
Section: Discussionsupporting
confidence: 90%
“…The considerably low TRC obtained by Grace and Ally [1973] among the Zulus is, however, not seen in our studies among the Southern Nigerian Negro. The TRC in Zulu males and females were 129.9 ± 45.7 and 119.6 ± 49.6, respectively, while the Nige rian figures were 143.3 ± 43.3 and 130.5 ± 51.5.…”
Section: Discussioncontrasting
confidence: 98%
“…This finding is in agreement with those of Grace and Ally [1973] in their studies among the Zulus of South Africa. Even though Grace and Ally attributed this surprising finding to sampling error, our studies which confirms theirs may indicate that sex difference in atd angles is a feature of 'Negro-dermatoglyphics.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Parents of all investigated subjects are healthy and of the same ethnic group. Three samples are used as outgroups: Africans [28], [29], Caucasians [3], and Gin Vietnamese [30]. 121 samples from 56 ethnic groups in China as shown in Table 1 contain a total of 68,846 individuals with 35,950 males and 32,896 females (excluding Indian Tibetans (T.B.-1)) [16].…”
Section: Methodsmentioning
confidence: 99%